Revitalisasi Peran Ushul Fiqh sebagai Landasan Metodologis Istinbath Hukum dalam Islam - Rafiq, M. (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2007)
The article below presents a critical review on modern tendencies of Islamic jurisprudencial thinking that promotes to the reformation of Islam body of law. The author want to propose a assimilative perspective between classical herritage of Islam jurispruclencial methods, and that of modern one. This article primarily is based on author s thesis on Quran s paradigm of dilalah, that was promoted at Master Prograrnme of IAIN Al-Raniri Darussalam, Aceh, in 2003.